Phototransistors with Negative or Ambipolar Photoresponse Based on As-Grown Heterostructures of Single-Walled Carbon Nanotube and MoS2 - Nguyen, Van Tu; Yim, Woongbin; Park, Sae June; Son, Byung Hee; Kim, Young Chul; Cao, Thi Thanh; Sim, Yumin; Moon, Yoon Jong; Nguyen, Van Chuc; Seong, Maeng Je; Kim, Sun Kyung; Ahn, Yeong Hwan; et al. (Advanced Functional Materials, 2018)
A facile synthesis method for the heterostructures of single-walled carbon nanotubes (SWCNTs) and few-layer MoS2 is reported. The heterostructures are realized by in situ chemical vapor deposition of MoS2 on individual SWCNTs. Field effect transistors based on the heterostructures display different transfer characteristics depending on the formation of MoS2 conduction channels along SWCNTs. Under light illumination, negative photoresponse originating from charge transfer from MoS2 to SWCNT is observed while positive photoresponse is observed in MoS2 conduction channels, leading to ambipolar photoresponse in devices with both SWCNT and MoS2 channels. The heterostructure phototransistor, for negative photoresponse, exhibits high responsivity (100–1000 AW−1) at low bias voltages (0.1 V) in the visible spectrum (500–700 nm) by combining high mobility conduction channel (SWCNT) with efficient light absorber (MoS2).
Keywords: Conduction channel; Facile synthesis; Light illumination; Low bias voltage; MoS2; Single-walled carbon nanotube (SWCNTs); Transfer characteristics; Visible spectra; carbon nanotubes; heterostructures; MoS2; phototransistors